Rbpms2 prevents major cardiac defects in cardiomyocyte-specific Rbpms-deficient mice - Lin, Shan; Dieterich, Christoph; Britto-Borges, Thiago; Günther, Stefan; Kreher, Silke; Eibach, Yvonne; Kuenne, Carsten; Schneider, Andre; Braun, Thomas (Developmental cell, 2025)
Cell-type-specific splicing depends on RNA-binding splicing factors. Several important splicing factors were identified in cardiomyocytes, including members of the RNA-binding proteins with multiple splicing (RBPMS) family, but their role during heart development has not been fully characterized. Here, we demonstrate that the function of RBPMS overlaps with the closely related paralog RBPMS2. Rbpms-deficient cardiomyocytes exhibit a higher degree of binucleation at birth, but this does not affect heart function in mice substantially until late adulthood. In contrast, Rbpms/Rbpms2 (Rbpms/2) compound mutants show pronounced disruption of the splicing network in embryonic cardiomyocytes, which leads to the formation of defective nuclei and disruption of sarcomere structures, eventually resulting in embryonic lethality. We demonstrate that mitotic defects in embryonic Rbpms/2-deficient cardiomyoctes are caused by the disbalance of nuclear and cytoplasmic calcium (Ca2+)/CaM-dependent protein kinase II gamma (Camk2g) isoforms. Overexpression of the Rbpmsa isoform partially rescues these defects, preventing embryonic lethality of Rbpms/2-deficient mice, and is sufficient for cardiomyocyte-specific splicing in other cell types.